Money, development and economic transformation : - Riese, Hajo (Palgrave Macmillan, 2004)
Hajo Riese has been Professor of Economics at the Free University Berlin since 1971. He was Vice-President of the University from 1973 to 1975 and directed the Institute for Theory of Economic Policy until 2001. In his main field of research, monetary economics, he advised the central banks and governments of many developing countries such as Ecuador, Bolivia and Vietnam. Money, Development and Economic Transformation presents a selection of thought-provoking essays by Hajo Riese that have not previously been available in English. Riese's fundamental methodological position, formulated with particular reference to Keynes, provides new insights into major issues of economic development and economic transition. This makes these essays, selected by Riese himself, particularly valuable reading. The first two chapters lay the theoretical foundations by explaining how a monetary economy works and the role of monetary policy, with specific reference to Bagehot and Keynes respectively. The implications of Riese's analysis are of the utmost importance for countries in the process of transition towards a capitalist system. Riese demonstrates in the following chapters that strategies of economic development and economic transition will fail if the requirements of a monetary economy are not met.